Load frequency control using adaptive and fuzzy based controller for hybrid micro-grid system - Mahdi, Mazin Mustafa (2018)
A hybrid micro-grid is a subset and becomes vital in the modern power grid, which is using inertia and non-inertia Distributed Generations (DGs) to supply power to communities in the small-scale area rather than vast regions. A micro-grid can operate in synchronous with the grid utility or as islanding; it is a useful method of achieving network expansion but have some issues. The transfer mode from the local main grid to islanding mode faces many challenges, related to significant load changes suddenly and the loss of the main electricity grid. When the micro-grid is disconnected, and in islanded mode, the active and reactive power needs to be controlled by the DG units. This research report includes an analysis of Load Frequency Control (LFC) for control of a hybrid micro-grid connected to the grid, and when operating in islanded mode. The benefit of this method of control is to correct frequency deviations during conditions of islanded operation as the DG would continually inject power at the desired level. The micro-grid control strategies investigated in this work included an analysis of the transient response of the frequency deviation and power sharing in both grid-connected and islanded modes of micro-grid operation. The adaptive PI controller is utilized by applying a Model Reference Adaptive Control (MRAC) based MIT rule for a smooth transfer micro-grid from the local main grid to the islanded mode for avoiding high-frequency deviations. Then, an Artificial Neural Network (ANN) controller is used to update the output of MRAC and to enhance micro-grid operation performance. From the simulation studies, it is clear that MRAC-ANN based controller can effectively damp out the oscillations and reduce the settling time. The Fuzzy Logic Table Control (FLTC) is employed in LFC at islanded micro-grid system to regulate the system's frequency, and provides desirable performance against sudden load changes and fault disturbances, improving the frequency deviation and output power variation. For verification, all the analyses are compared with conventional PI controller and the results show the proposed controller outperform the conventional PI controller in promising response. The proposed controller can classify simple and easy to implement. Therefore, these proposed controllers of LFC can contribute to the expanding the energy utilization into the micro-grid environment.